Determinants on service quality that affecting customer’s satisfaction in insurance industry / Nurul Nadia Yusof - Yusof, Nurul Nadia (2010)
The important issue of this research is to determine on service quality that affecting customer’s satisfaction in insurance industry. These means is there any relationship between all the independent variables with the dependent variable. This research basically focuses on the insurance policyholder, mostly MAA Assurance policyholders’ in Johor Bahru branch. A framework was developed and tested whereby customer’s satisfaction is influenced by three elements of service quality which are service products, service delivery and service environments. There several problems for insurance industry today where most of the policyholders are not satisfied with the service given by insurance company. So that, the researcher tried to clarify what factors that can contribute to this matter. The research is being narrowed to 50 and randomly chosen respondents as the data sampling in order to identify whether the service quality dimensions has a relationship towards customer’s satisfaction. The findings and analysis were based on the data obtained from the questionnaire responses. The analysis of findings involved the use of Cronbach’s Alpha to measure the reliability of data and descriptive statistics that consist of frequency distributions. Furthermore, the correlation was used to see if there are any significance differences in the means for all variables of interest. F Statistic has been carried out in order to determine whether there is a significant different between each individual selected demographic factors. Finally the findings of this research are useful to determine on service quality that affecting customer’s satisfaction in insurance industry.